Implementation of an ultrasonic tomograph for small specimens. (June 2019) - Villarreal, A; Huerta, F; Solis-Najera, S; Medina, L
Abstract: The implementation of an open freeware to acquire and reconstruct ultrasonic images from tomographic projections is presented. This proposed tomograph consists of three main modules: the mechanical position system, control system and the ultrasonic pulse emission-reception system. The communication, synchronization among these modules, experimental parameters and image reconstruction are done by an interface based on JAVA. The preliminary results show that the system is able to produce quality images of tested specimens.